Lattice Boltzmann Method for Wave Propagation in Elastic Solids (Communications in Computational Physics, 2020)
We present a new lattice Boltzmann formulation for elastic solids and analysethe issue of conservation laws for solids. This new formulation allows tunablePoisson ratio. As a first benchmark problem, we consider an elastic wave propagatingin an infinite homogeneous medium with point force and point dipole Ricker waveletas the source. The method is successful in simulating behavior of elastic wave motionas a function of Poisson ratio.
Keywords: Lattice Boltzmann Method; elastic solids; Poisson ratio.